2020
DOI: 10.1155/2020/4373401
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Metabolomics Profiling of Torch Ginger (Etlingera elatior Jack) Flower Oil Extracted Using Subcritical Carbon Dioxide (CO2)

Abstract: The aim of this study was to identify the bioactive compound and evaluate the antibacterial activity of torch ginger flower oil extracted using subcritical carbon dioxide. The antibacterial activity was evaluated in agar diffusion assay, while MIC and MBC were determined using the microdilution broth assay. The essential oil was subjected to metabolomics profiling using GC-MS and 1H-NMR techniques. The results demonstrated strong antibacterial activity towards Salmonella typhimurium, Staphylococcus aureus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
2
5
0
3
Order By: Relevance
“…1). The results were in agreement with those of Anzian et al [17], who reported that oil extracts of torch ginger (Etlingera elatior Jack) flower using subcritical carbon dioxide (CO 2 ) exhibited very strong antibacterial activity against S. aureus (14.50 ± 2.21 mm). Research by Susanti et al [18] showed that the 10 μL concentration of torch ginger flower essential oil could provide 6 mm inhibition in S. aureus bacteria.…”
Section: Antibacterial Activitysupporting
confidence: 92%
See 2 more Smart Citations
“…1). The results were in agreement with those of Anzian et al [17], who reported that oil extracts of torch ginger (Etlingera elatior Jack) flower using subcritical carbon dioxide (CO 2 ) exhibited very strong antibacterial activity against S. aureus (14.50 ± 2.21 mm). Research by Susanti et al [18] showed that the 10 μL concentration of torch ginger flower essential oil could provide 6 mm inhibition in S. aureus bacteria.…”
Section: Antibacterial Activitysupporting
confidence: 92%
“…The EFs of torch ginger contained 19 compounds, with Dodecanoic acid (18.60%) being the most abundant (Table 1). The (E)-5-Tetradecene, 1-Tetradecyl acetate, Cyclotetradecane, Tetradecanoic acid, Cyclotetradecane, n-Hexadecanoic acid, Tricosane, Dodecanoic acid, and Dodecyl ester were similar to the previous reports [2,[17][18][20][21].…”
Section: Metabolites Profilessupporting
confidence: 89%
See 1 more Smart Citation
“…The oil of the torch ginger flower, extracted with subcritical carbon dioxide (CO2), has a lot of potential as a natural antibacterial agent in pharmaceutical and food applications. After 12 months of storage at 8°C, the extracted oil's antibacterial activity remained quite stable (Anzian et al, 2020). Preliminary study by Syafriana et al (2021) resulted that Staphylococcus epidermidis and Propionibacterium acnes can be inhibited by an ethanol extract of torch ginger flower.…”
Section: Antimicrobial Activitymentioning
confidence: 97%
“…In Malaysia, particularly in Borneo, E. elatior has widely been used as a traditional remedy for stomachache, food poisoning, and gastric problems (Guzzo et al, 2020). The inhibitory activities of E. elatior extracts against Gram-positive bacteria including S. aureus have previously been reported (Chan et al, 2011;Anzian et al, 2020). However, the efficacy of E. elatior against the biofilm formation by S. aureus remains uncertain.…”
mentioning
confidence: 99%